Diazotrophs and N2-Fixation Associated With Particles in Coastal Estuarine Waters - Pedersen, Jeppe N.; Bombar, Deniz; Paerl, Ryan W.; Riemann, Lasse (Frontiers in Microbiology, 2018)
Putative heterotrophic bacteria carrying out N2-fixation, so-called non-cyanobacterial diazotrophs (NCDs), are widely distributed in marine waters, but details of how the O2-inhibited N2-fixation process is promoted in the oxic water column remains largely ambiguous. In this study we carried out two experiments with water from a eutrophic temperate fjord to examine whether low-oxygen microenvironments within particulate organic matter could be loci suitable for N2-fixation by these bacteria. First, water enriched with natural particles or sediment showed higher N2-fixation rates than bulk water, and nitrogenase genes (nifH) revealed that specific diazotrophs were affiliated with the particulate matter. Second, pristine artificial surfaces were rapidly colonized by diverse bacteria, while putative diazotrophs emerged relative late (after 80 h) during the colonization, and phylotypes related to Pseudomonas and to anaerobic bacteria became dominant with time. Our study pinpoints natural particles as sites of N2-fixation, and indicates that resuspension of sediment material can elevate pelagic N2-fixation. Moreover, we show that diverse natural diazotrophs have the ability to colonize artificial surfaces, but colonization by ‘pioneer’ bacterioplankton that more rapidly associate with surfaces appears to be a prerequisite. Whereas our experimental study supports the idea of pelagic particles as sites of N2-fixation by heterotrophic bacteria, future in situ studies are needed in order to establish identity, activity and ecology of particle associated NCDs as a function of individual particle characteristics.